Exploring the emissive properties of new azacrown compounds bearing aryl, furyl or thienyl moieties: a special case of chelation enhancement of fluorescence upon interaction with Ca2+, Cu2+ or Ni2+ - Oliveira, Elisabete (2010)
Three new compounds bearing furyl, aryl or thienyl moieties linked to an imidazo-crown ether system (1, 2 and 3) were synthesized and fully characterized by elemental analysis, infrared, absorption and emission spectroscopy, X-ray crystal diffraction, and MALDI-TOF-MS spectrometry. The interaction towards metal ions (Ca2+, Cu2+, Ni2+ and Hg2+) and F- has been explored in solution by absorption and fluorescence spectroscopy. Mononuclear and binuclear metal complexes using Cu2+ or Hg2+ as metal centers have been synthesized and characterized. Compounds 2 and 3 show a noticeable enhancement of the fluorescence intensity in the presence of Ca2+ and Cu2+ ions. Moreover compound 3 presents a dual sensory detection way by the modification of the fluorimetric and colorimetric properties in the presence of Cu2+ or Hg2+. The EPR studies in frozen solution and in microcrystalline state of the dinuclear Cu(II)2 complex revealed the presence of an unique Cu2+ type.